2015
DOI: 10.1177/1535370215573400
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of programmed cell death factor 4/nuclear factor-κB signaling pathway in porcine coronary micro-embolization-induced cardiac dysfunction

Abstract: The aim of this study was to investigate the role of the programmed cell death factor 4 (PDCD4)/nuclear factor-kB (NF-kB) signaling pathway in coronary micro-embolism (CME)-induced inflammatory responses and cardiac dysfunction in a porcine model. Bama miniature pigs were randomly divided into four groups (n ¼ 5 per group). Micro-embolization balls or saline were infused through a microcatheter in the left anterior descending (LAD) artery in the CME and Sham groups, respectively. PDCD4 siRNA or control siRNA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The probe frequency was 12 MHz. All values were the average measurements of three cardiac cycles 31 . Echocardiographic data were recorded and analyzed by blinding to different treatments.…”
Section: Methodsmentioning
confidence: 99%
“…The probe frequency was 12 MHz. All values were the average measurements of three cardiac cycles 31 . Echocardiographic data were recorded and analyzed by blinding to different treatments.…”
Section: Methodsmentioning
confidence: 99%
“…NF-κB activation serves a critical role in coronary microembolism-induced cardiac dysfunction and advanced heart failure ( 18 ). For example, NF-κB activation and the subsequent inflammatory response contribute to cardiac dysfunction and maladaptive left ventricular remodeling following MI ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 We previously found that CME-induced activation of PDCD4/NF-κB/TNF-α pathway had an important role in CME-induced myocardial inflammatory responses. 5 Overexpression of microRNA-21 in cardiomyocytes regulates its target genes to exert anti-inflammatory and antiapoptotic effects resulting in myocardial protection. Animal experiments confirmed that ischemic preconditioning significantly upregulated microRNA-21 expression and downregulated its target gene PDCD4 to prevent the PDCD4-mediated activation of activated protein-1 and myocardial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of PDCD4/NF-κB/TNF-α pathway reduced CME-induced myocardial damage and improved cardiac function. 5 It has been recently reported that microRNA-21 exerts a protective effect on myocardium mainly through the regulation of PDCD4-mediated antiapoptotic and anti-inflammatory pathways. 6 Therefore, we speculated that transfection of microRNA-21 into myocardium to regulate PDCD4 expression could potentially inhibit CME-induced activation of PDCD4/NF-κB/ TNF-α pathway and protect the myocardium.…”
Section: Introductionmentioning
confidence: 99%